Political and legal ideas of the Syrym Datuly (Journal of actual problems of jurisprudence, 2018)
The article deals with the political and legal views of Batyr and Biy Syrym Datuly. Expansion of the expansionist policy of Russia in Kazakhstan expanded combat dynasty Abuhair Khan Junior Zhuz. Syrym Datuly during their struggle was based not only on the idea of national liberation but also on the idea of the unity of the Turkic peoples. On the basis of these ideas lay distrust dynasty and protect the interests of the general public.Key words: Pan-Turkism, the dynasty, Khan’s power, expansion.